2021
DOI: 10.1515/cclm-2021-0455
|View full text |Cite
|
Sign up to set email alerts
|

IFCC interim guidelines on rapid point-of-care antigen testing for SARS-CoV-2 detection in asymptomatic and symptomatic individuals

Abstract: With an almost unremittent progression of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections all around the world, there is a compelling need to introduce rapid, reliable, and high-throughput testing to allow appropriate clinical management and/or timely isolation of infected individuals. Although nucleic acid amplification testing (NAAT) remains the gold standard for detecting and theoretically quantifying SARS-CoV-2 mRNA in various specimen types, antigen assays may be considered a suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 62 publications
0
15
0
1
Order By: Relevance
“…Recent guidelines published by the World Health Organization (WHO) and the Task Force on COVID-19 of the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) [ 10 , 11 ] have suggested the potential use of antigen rapid tests in biological materials, in particular NP samples and saliva, for mass testing. Antigen-based assays use monoclonal anti-SARS-CoV-2 antibodies, which recognize SARS-CoV-2 antigens, mainly N and S (Nucleocapsid protein and Spike surface glycoprotein, respectively) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent guidelines published by the World Health Organization (WHO) and the Task Force on COVID-19 of the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) [ 10 , 11 ] have suggested the potential use of antigen rapid tests in biological materials, in particular NP samples and saliva, for mass testing. Antigen-based assays use monoclonal anti-SARS-CoV-2 antibodies, which recognize SARS-CoV-2 antigens, mainly N and S (Nucleocapsid protein and Spike surface glycoprotein, respectively) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…≥0.97) and acceptable sensitivity (i.e. ≥0.80) [ 10 , 11 ]. Indeed, it is pivotal that such tests give reliable and reproducible results.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic accuracy of Ag-RDTs has been thoughtfully reviewed by many recent meta-analyses, which revealed that their sensitivity compared to reference molecular techniques is considerably low, typically in the range of 0.59-0.76 [ 6 ], 0.66-0.88 [ 7 ], or 0.57-0.71 [ 8 ] depending on the different populations and according to the distinct strategy used for pooling data. Therefore, although they can be rapidity performed outside of conventional clinical laboratories, the low accuracy does not enable efficient triage of COVID-19, leaving under-diagnosed up to one-third of subjects with SARS-CoV-2 infection [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In these settings, a Ag-RDT positive should be considered preliminary, with individuals isolating until a PCR test result is known. Ag-RDT negative individuals should continue to comply with conventional risk mitigation measures [ 10 ]. Ag-RDTs will be most effective when used regularly, with high levels of participation.…”
Section: Introductionmentioning
confidence: 99%